Research Advance of the Failure Mechanism and Friction Wear of Flexible Wheel of Harmonic Reducer - Xia Tian; Jiang Peng; Ma Chao; Chen Wei; Yan Ruiping (Jixie chuandong)
The main reason for the transmission performance degradation of harmonic reducer is the wear of flexible wheel,and the research of failure mechanisms of flexible wheel provides a reference for design and manufacture of harmonic reducer. By research progress introduction of space lubrication and failure mechanisms of harmonic drive reducer at home and abroad,comparing the research results of different lubrication method,then the existing problems of wear failure mechanism of flexible wheel and its future research direction of friction and wear mechanism are proposed.